Re-narrating and re-masculating the 'brute' in the first season of eKasi: our stories - Sulelo, Nande (My University, 2016)
Hollywood has always paid much attention to black masculinity; depicting black males in ways that demean them to keep them as subordinates. This stereotypical representation of black men, especially in the townships, has been one that South African filmmakers have subscribed to with the constant portrayal of black men as ‘as animals, brutes, natural born rapists, and murderers’ (hooks 2004). A study of e.tv’s short film series, eKasi: Our Stories, will illustrate how this series typifies what Morrell refers to as ‘new masculinities’ and furthermore explores black masculinities as multitudinous as “there are many characteristics and experiences that define black men” (Whiting & Lewis 2008). The first season of the series, with five episodes will be critically studied to demonstrate how black masculinities have been reimaged by the filmmakers of these short films. These short films open up spaces for various identities for black men by affording the characters complexity. This will be showcased with a careful examination of the themes of these five stories. Also of equal importance is the characterisation of the black male characters in relation to others and their communities. The study focuses on how the revision of the black man from the township gives back to him the humanity, dignity and most notably masculinity which he had been stripped off since his first appearance on film and television. By employing Harris’ (2006) notion of a New Black Cinema, it will be demonstrated that the short film series is in line with emerging theories of the revision of the black image onscreen.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Arts. Wits University, Johannesburg, 2015